Sekolah Inklusi antara Kenyataan dan Realita - Sri Ayu Irawati (Magister Pendidikan Nonformal Pascasarjana Universitas Negeri Gorontalo, 2023)
The need for inclusive schools in modern times has increased according to data on the number of students for according to statistical data published by the Coordinating Ministry for PMK in June 2022, the disability range for children aged 5-19 years is 3.3%. Meanwhile, the population at that age (2021) is 66.6 million people. Thus, the number of children aged 5-19 years with disabilities ranges from 2,197,833 people. Then, data from the Ministry of Education and Technology as of August 2021 shows that the number of students in the Special and Inclusive School (SLB) pathway is 269,398 children. With this data, the percentage of children with disabilities who take formal education is only 12.26%. This means that there are still very few children with disabilities or children with special needs (ABK) in Indonesia who should get access to inclusive education, even though from year to year the number continues to increase. The increasing number of students with special needs from year to year in this case will make the need for advice and educational infrastructure for children with needs increase. Inclusion education according to Garnida (2015: 48) defines inclusive education, namely the education delivery system for students who have certain limitations and other students who are made one without considering their respective limitations. which in this case means collaboration in education between children in the general category with children with special needs who in the category are able to sit side by side even though it is possible with the facilities of accompanying teachers.the presence of inclusion schools will further expand opportunities for students to develop and improve their abilities together with their peers who will further support the mindset and way of socializing, two things that sometimes become obstacles within existing limitations. Considering the existing situation coupled with the variety of characteristics and demands of increasingly varied needs so that it can be a reference for the government to be able to further increase the presence of inclusive schools among us. The reality on the ground is that there is no match between the number of students with special needs and the school or educational facilities prepared. It takes the ability to handle it and acceptance from society to be able to accept every citizen with all his character and ability, for this reason the author takes the title of School of Inclusion between Reality and Reality.